The Earth is getting hotter urban inferno and outsider women’s collectives in Bumi Makin Panas - Yngvesson, Dag (2014)
Access online through this link: https://www.plarideljournal.org/article/the-earth-is-getting-hotter-urban-inferno-and-outsider-womens-collectives-in-bumi-makin-panas
Keywords: Film criticism; Indonesia